Synthesis and Spectral Studies of Some Novel Derivatives of 1,5-Benzothiazepines - Nigam, Sandeep; Joshi, Y.C. (Asian Journal of Chemistry, 2016)
The title compounds 3a-i, of potential pharmacological interest, have been obtained by condensation of ring substituted propane-1-(1,3-benzodioxol-5-yl)-3-phenyl-1,3-diones 2a-i with 2-amino-benzenethiols 1a-b, in pyridine. Compounds were analyzed by elemental analysis, IR, 1H NMR, 13C NMR and mass spectral studies.